Clostridium difficile acquisition rate and its role in nosocomial diarrhoea at a university hospital in Turkey - (:unkn) unknown (SPRINGER, 1996)
Infection with Clostridium difficile can present with various clinical pictures ranging from an asymptomatic carrier state to pseudomembranous colitis and plays an important part in the etiology of nosocomial diarrhoea. To identify risk factors for C. difficile colonization and diarrhoea in hospitalized subjects, patients admitted to a general medicine ward at Marmara University hospital during a one year period were entered into the study. Of the 202 patients, nosocomial diarrhoea developed in 45 (22.3%). Fourteen patients (6.9%) were colonized with C. difficile during their hospitalization period. Ten of the colonized patients (71.4%) developed diarrhoea and were found to be positive by toxin assay. Pseudomembranous colitis was confirmed endoscopically in 3 of the patients with diarrhoea. Administration of beta lactam agents such as ampicillin and cephalosporins; gastrointestinal manipulations and admission to the intensive care unit were found as major risk factors for C. difficile colonization.
Keywords: Clostridium difficile; pseudomembranous colitis; nosocomial diarrhoea; RISK-FACTORS; COLITIS; ADULTS